PENERAPAN MODEL PEMBELAJARAN KOOPERATIF UNTUK MENINGKATKAN KETERAMPILAN MEMBUAT BENDA KONTRUKSI DARI KERTAS KORAN SISWA KELAS IV SD NEGERI 009 RAMBAH - Julianti, Depi; Kurniaman, Otang; ', Guslinda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The problems in this study is whether the implementation of cooperative learning model can improve the skills to make objects construction of newsprint students class 4 in SD Negeri 009 Rambah. While the purpose of this research is to improve the skills of making objects newsprint construction of students class 4 of SD Negeri 009 Rambah with the implementation of cooperative learning model. The subjects were students class 4 of SD Negeri 009 Rambah Academic Year 2015/2016, with 16 students with 11 male and 5 female students. Data collection instrument in this study is the observation sheet teachers, product or outcome assessment rubric, and scoring rubric process. The result showed that the skills assessment data to make objects of construction on the initial data with the average value of 55.75 increased by 32.37% up on the first cycle obtained by the average value of 73.80. In the second cycle amounted to 46.29% in order to obtain an average value of 81.56. Increased activity of teachers at the first meeting of the first cycle by 75 percentage teacher activity in good category, the second meeting of the first cycle of 79.1 good category. Cycle II activities 83.3 teachers with excellent category. The second meeting of the second cycle of activity 87.5 teachers with excellent category. Increased activity of the first meeting of the first cycle students 62.5% to the category enough, the second meeting of the first cycle of 75% with both categories. At the first meeting of the second cycle of 79.1% in both categories. At the second meeting of the second cycle of 83.3% with a good category.Key Words : Cooperative Learning Model, Construction of objects from Newsprint